2019
DOI: 10.1186/s40249-019-0615-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of malaria rapid diagnostic tests: a systematic review

Abstract: BackgroundRapid diagnostic tests (RDT) can effectively manage malaria cases and reduce excess costs brought by misdiagnosis. However, few studies have evaluated the economic value of this technology. The purpose of this study is to systematically review the economic value of RDT in malaria diagnosis.Main textA detailed search strategy was developed to identify published economic evaluations that provide evidence regarding the cost-effectiveness of malaria RDT. Electronic databases including MEDLINE, EMBASE, Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
(127 reference statements)
1
32
0
Order By: Relevance
“…Furthermore, compared to microscopy or PCR, the diagnostic cost of RDTs is relatively low, with a low cost of RDT strips and the training fees for laboratory staff. A few studies have been undertaken to evaluate the economic value of RDTs and they demonstrated that in comparison with microscopy, RDTs are more cost-effective if the whole treatment course have been taken into account [78][79][80]. Therefore, as most of the malaria-endemic areas have limited resources, RDTs is of high value to be used there.…”
Section: Viewpoints Papersmentioning
confidence: 99%
“…Furthermore, compared to microscopy or PCR, the diagnostic cost of RDTs is relatively low, with a low cost of RDT strips and the training fees for laboratory staff. A few studies have been undertaken to evaluate the economic value of RDTs and they demonstrated that in comparison with microscopy, RDTs are more cost-effective if the whole treatment course have been taken into account [78][79][80]. Therefore, as most of the malaria-endemic areas have limited resources, RDTs is of high value to be used there.…”
Section: Viewpoints Papersmentioning
confidence: 99%
“…8 There is only one published empirical economic evaluation of RDT introduction in the SSA retail sector, 18 which reports cost-effectiveness in terms of intermediate outcomes (cost per appropriately treated patient) 18 rather than final health outcomes (such as disabilityadjusted life years (DALYs) averted). 19 To our knowledge, this paper is the first to model the cost-effectiveness of subsidised malaria RDT introduction in the SSA private sector. Unlike a single empirical study, a modelling approach enables exploration of costeffectiveness under a range of treatment practices, and varying levels of malaria transmission, as well as assessing sensitivity to the many other model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In sub-Saharan Africa, RDT has now become the most widelyused method for malaria diagnosis among suspected patients in public healthcare institutions [2]. However, previous economic evaluations of RDT were mainly performed in Africa, there was very little evidence from the elimination setting [10]. Moreover, many factors that impact the result of a cost-effectiveness analysis (CEA), such as incidence rate, the distribution of Plasmodium species, labor cost, and health workers' awareness of malaria, were very different in different areas [11,12].…”
Section: Introductionmentioning
confidence: 99%